Rethinking the Top-Down Approach to Schistosomiasis Control and Elimination in Sub-Saharan Africa - Onasanya, Adeola; Bengtson, Michel; Oladepo, Oladimeji; Van Engelen, Jo; Diehl, Jan Carel (Frontiers in Public Health, 2021)
The control and elimination of schistosomiasis have over the last two decades involved several strategies, with the current strategy by the World Health Organization (WHO) focusing mainly on treatment with praziquantel during mass drug administration (MDA). However, the disease context is complex with an interplay of social, economic, political, and cultural factors that may affect achieving the goals of the Neglected Tropical Disease (NTD) 2030 Roadmap. There is a need to revisit the current top-down and reactive approach to schistosomiasis control among sub-Saharan African countries and advocate for a dynamic and diversified approach. This paper highlights the challenges of praziquantel-focused policy for schistosomiasis control and new ways to move from schistosomiasis control to elimination in sub-Saharan Africa. We will also discuss an alternative and diversified approach that consists of a systems thinking framework that embraces intersectoral collaboration fully and includes co-creating locally relevant strategies with affected communities. We propose that achieving the goals for control and elimination of schistosomiasis requires a bottom-up and pro-active approach involving multiple stakeholders. Such a pro-active integrated approach will pave the way for achieving the goals of the NTD 2030 roadmap for schistosomiasis, and ultimately improve the wellbeing of those living in endemic areas.